2009
DOI: 10.1519/jsc.0b013e3181a00d62
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Partner's Improvisational Resistance Training on Dancers' Muscular Strength

Abstract: The purpose of this study was to observe the effects of Partner's Improvisational Resistance Training (PIRT) on muscular strength, body circumference, and body fat percentage in 10 female college-age dancers in comparison with 8 female dancers in a control group. The PIRT program, based on the concepts of manual resistance training, is the application of contact improvisation in a systematic strength development program, which proposes a way of contextualizing muscular strength development within the dance cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 16 publications
0
17
0
2
Order By: Relevance
“…To establish an effective training position or exercise set-up for MRT only limited equipment is necessary, which may include benches, chairs, tables, step boxes, PVC pipes and straps. The application of MRT in adults has been shown to result in improved fitness and muscular strength (7,19,27), and improvements may be comparable to those achieved through traditional weight resistance training (8). However, no known data exists for this training method in adolescents.…”
Section: Introductionmentioning
confidence: 99%
“…To establish an effective training position or exercise set-up for MRT only limited equipment is necessary, which may include benches, chairs, tables, step boxes, PVC pipes and straps. The application of MRT in adults has been shown to result in improved fitness and muscular strength (7,19,27), and improvements may be comparable to those achieved through traditional weight resistance training (8). However, no known data exists for this training method in adolescents.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the percent-increase rate of the group with high muscle strength was lower than that of the group with low muscle strength. Although the number of prior studies which have focused only on the effects of MRT is limited, the effects of MRT on increase in muscle strength were reported [14][15][16] . Vetter et al 15) and Dorgo et al 16) employed university students who obviously have higher muscle strength than elderly people in their study.…”
Section: Discussionmentioning
confidence: 99%
“…However, we could find no study in the literature which solely observed the effects of MRT among elderly people. We found only a few studies, such as a case study of patients with muscle dystrophy and an intervention study with young adults as subjects [14][15][16] . This meant that components of MRT, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…However, considering that only a small portion of the world population attend gyms 5 , recent studies have suggested alternative forms that do not depend on equipment in order to permit the application of RT in nonspecific environments and places such as residential condominiums, hospitals, clinics, basic health units, universities, schools, and companies, among others [6][7][8][9] . One alternative of RT that is being investigated is manual resistance training (MRT) [7][8][9][10] , a concept that uses manual resistance imposed by a second person in the direction opposite to the movement performed by the exercising subject ( Figure 1A, 1B). Previous studies have shown that MRT is effective in increasing strength levels in different populations [7][8][9][10] .…”
Section: Introductionmentioning
confidence: 99%
“…One alternative of RT that is being investigated is manual resistance training (MRT) [7][8][9][10] , a concept that uses manual resistance imposed by a second person in the direction opposite to the movement performed by the exercising subject ( Figure 1A, 1B). Previous studies have shown that MRT is effective in increasing strength levels in different populations [7][8][9][10] . Furthermore, the effects of MRT are similar to those of free weight resistance training (FWRT) as long as the volume and intensity are comparable 7,11 .…”
Section: Introductionmentioning
confidence: 99%